Kastanozems in the Otjiwarongo Region (Namibia): pedogenesis, associated soils, evidence for landscape degradation - Eitel, Bernhard; Eberle, Joachim (ERDKUNDE, 2001)
The paper deals with Kastanozem formation, with associated dark soils like Vertisols and Calcisols which have thick humic epipedons and with actual erosional processes in the Otjiwarongo region The Kastanozem soil associations occur as patches of several hundreds of hectares. Important pedogenetic factors were fine-grained host sediments, the semi-arid climate, a dense savanna grass cover and geomorphic stability. The Kastanozems show gradual transitions to Calcisols on slopes and on tops due to a decreasing amount of soil-organic matter and increasing carbonate content, and to Vertisols in the lowest positions of the relief due to an increasing amount of smectites in the clay fraction. The dark savanna soils are an important natural resource of the region because they are very fertile and have high water retention capacity. At present soil degradation is the most remarkable process affecting the pedosphere in the study area. In a first phase most of the Kastanozems and Vertisols are buried by slope wash sediments up to several decimeters. Actually this soil association is affected by rill and gully erosion indicating an increased run-off.